Formation of high power microwave pulses with adjustable parameters in active X-band RF compression systems; Micro/Nanotechnologies and Electron Devices (EDM) - Avgustinovich V. A. Vladimir Andreevich; Artemenko S. N. Sergey Nikolaevich; Igumnov V. S. Vladislav Sergeevich; Yushkov Y. G. Yuri Georgievich (2015, 2015)
Title screen